Fabrication of PLA incorporated chitosan nanoparticles to create enhanced functional properties of cotton fabric. Issue 2 (26th October 2018) - Ali Raza, Zulfiqar; Anwar, Faiza; Hussain, Irshad; Abid, Sharjeel; Masood, Rashid; Shahzad Maqsood, Hafiz
Abstract : Purpose: This study aimed to present fabrication of novel poly(lactic acid) (PLA) mediated chitosan nanoparticles (CNPs) and their impregnation on cotton fabric for enhanced antibacterial and physical properties. Design/methodology/approach: The PLA-CNPs were characterized using scanning electron microscopy, energy dispersive x-ray spectroscopy, Fourier transform infrared (FTIR) spectroscopy and zeta size analysis. The prepared PLA-CNPs were impregnated on cotton fabric via pad-dry-cure method. The finished cotton fabric was then characterized for its antibacterial activity, functional and other physical textile properties. Findings: The spectral and optical properties demonstrate that the NPs expressed spherical morphologies with an average particle diameter of 88.02 nm. The antibacterial activity of treated fabrics ranged between 75 and 90 per cent depending on the concentration of PLA-CNPs. Practical implications: Because of enhanced awareness and desire for ecofriendly products, the use of sustainable and functional textiles is increasing day by day. For the said purpose, industries are using different chemical treatments to achieve desired end functionality. Currently, different synthetic antibacterial agents are in practice, but they lack sustainable approach to save the environment. In this study, the researchers have developed PLA mediated CNPs for sustainable antibacterial and physical properties of treated cotton fabric. Originality/value: To the best of the authors' knowledge, this is first attempt to fabricate PLA-incorporated CNPs for application on cotton fabric followed by a detailed characterization.